Angupyrones A – E, α‐Pyrone Analogues with ARE‐Activation from a Sponge‐Associated Fungus Truncatella angustata. Issue 9 (18th August 2017) - Zhao, Yang; Liu, Dong; Proksch, Peter; Yu, Siwang; Lin, Wenhan
Abstract : TLC‐DPPH guided fractionation of a sponge‐associated fungus Truncatella angustata with a solid culture resulted in the isolation of five new α ‐pyrone‐based analogues namely angupyrones A – E (1  – 5 ), and 3‐ethyl‐4‐hydroxy‐6‐methyl‐2‐pyrone. Their structures were determined on the basis of extensive spectroscopic analyses, including the modified Mosher 's method, bulkiness rule, and specific rotation for the configurational assignments. Angupyrones A – E exhibited moderate antioxidant response element activation in HepG2C8 cells, while the preliminary structure‐activity relationship was discussed. Abstract :